From Massive Violations to Structural Patterns: New Approaches and Classic Tensions in the Inter-American Human Rights System - Abramovich, Victor (2009)
This article presents an overview of the main discussions taking place both within the Inter-American bodies and the human rights community about the role of the Inter-American Human Rights System in the political-regional scenario. The author begins the article by analyzing the issues addressed in the ISHR from its beginnings to the present day, highlighting that the bodies of the ISHR have transcended from focusing on the reparation of victims to the establishment of principles and standards that strengthen the protection of human rights. The author also analyzes the role of the ISHR bodies with respect to civil society activism in the area of human rights by virtue of the repercussions of the cases and situations on which they rule. It also reflects on the political debates that have arisen as a result of the recognition of rights and their positioning on the OAS agenda. Finally, the author analyzes the balance and imbalance between the political and judicial roles within the ISHR, as well as the effectiveness of the decisions issued by the bodies of the ISHR and their articulation in the national justice systems.